Activation therapy for the treatment of inpatients with depression – protocol for a randomised control trial compared to treatment as usual - Ian R. E. Averill; Ben Beaglehole; Katie M. Douglas; Jennifer Jordan; Marie T. Crowe; Maree Inder; Cameron J. Lacey; Christopher M. Frampton; Christopher R. Bowie; Richard J. Porter (BMC Psychiatry, 2019)
Abstract Background Inpatients with depression have a poor long term outcome with high rates of suicide, high levels of morbidity and frequent re-admission. Current treatment often relies on pharmacological intervention and focuses on observation to maintain safety. There is significant neurocognitive deficit which is linked to poor functional outcomes. As a consequence, there is a need for novel psychotherapeutic interventions that seek to address these concerns. Methods We combined cognitive activation and behavioural activation to create activation therapy (AT) for the treatment of inpatient depression and conducted a small open label study which demonstrated acceptability and feasibility. We propose a randomised controlled trial which will compare treatment as usual (TAU) with TAU plus activation therapy for adult inpatients with a major depressive episode. The behavioural activation component involves therapist guided re-engagement with previously or potentially rewarding activities. The cognitive activation aspect utilises computer based exercises which have been shown to improve cognitive function. Discussion The proposed randomised controlled trial will examine whether or not the addition of this therapy to TAU will result in a reduced re-hospitalisation rate at 12 weeks post discharge. Subjective change in activation and objectively measured change in activity levels will be rated, and the extent of change to neurocognition will be assessed. Trial registration Unique trial number: U1111–1190-9517. Australian New Zealand Clinical Trials Registry (ANZCTR) number: ACTRN12617000024347p.